MONUMENTS IN THE POST-SOCIALISTIC PERIOD: EXAMPLES FROM THE CITY-HERO IN MACEDONIA - Davorin Trpeski (EtnoAntropoZum, 2016)
Monuments contain a story or a message, i.e. they carry certain symbolism that reminds people to a certain glorified historical time, to an important event that people should remember. In short, they hide a certain ideology that interprets symbols, offers codes for their interpretation and establishes a tie with the already created myths. In authoritarian or totalitarian social systems monuments are the center of the public and political life. This article presents a part of the monuments characteristic for the town of Prilep during socialism, but also the newly created monuments after the fall of socialism and in the period of establishing the new social order in the Republic of Macedonia.